Obsessed maniacs and clairvoyant oracles: Empirically validated patterns of entrepreneurial behavior - Elias G. Carayannis; McDonald R. Stewart (Journal of Innovation and Entrepreneurship, 2013)
Diverse and complex challenges in new venture formation demand rare and exceptional entrepreneurial acumen, particularly in technology-driven environments where disrupted markets amplify the factors and magnitude of uncertainty and risk. The successful technology entrepreneur (term of art for Strategic Knowledge Arbitrage and Serendipity (SKARSE™) enactors) is focused yet flexible, demonstrating relentless intensity of purpose while adapting that purpose under changing conditions. The distinguished entrepreneur accurately predicts events and conditions in advance for superior strategic positioning. We find that two terse descriptors - obsessed maniacs and clairvoyant oracles- encapsulate critical attributes conducive to superlative entrepreneurial posture, propensity, and performance to anticipate and recognize challenges and convert them into opportunities. In so doing, the entrepreneurs leverage strategic knowledge serendipity factors and practice strategic knowledge arbitrage competences. From the pre-market perspectives of R&D and innovation management through successful marketing and commercialization of engineered innovations, technology foresight and forecasting pivot on the entrepreneur's unrelenting persistence to pursue a vision and unclouded prescience of exactly what vision to pursue. To investigate our premise, we conduct comprehensive surveys and interviews with 33 founding entrepreneurs, comparatively analyzing their experiences against complementary data sources to develop personal profiles of critical attributes and behavioral characteristics. Employing qualitative analytic techniques, we find the data rich in empirical evidence to support a perspective of entrepreneur as obsessed maniac and clairvoyant oracle, plus many other intrinsic characteristics of personality, motivation, intention, and action that constitute the entrepreneurial actor.
Keywords: 650; competitiveness; creativity; entrepreneurship; innovation; knowledge partnership; robust competitiveness; sustainable entrepreneurship; start-up; sustainable growth; technology adoption and diffusion